A Simple Method for Producing Colloidal Palladium Nanocrystals: Alternating Voltage‐Induced Electrochemical Synthesis. Issue 15 (19th February 2013) - Cloud, Jacqueline E.; McCann, Kevin; Perera, K. Alokya P.; Yang, Yongan
<x xml:space="preserve">Abstract</x> Alternating voltage‐induced electrochemical synthesis (AVIES) produces well‐dispersed, size‐controlled, single‐crystalline, colloidal palladium nanocrystals (Pd‐NCs). An alternating voltage is applied to two Pd wires inserted in an electrolyte solution containing capping ligands. Pd‐NCs are directly ejected from the Pd electrodes through cathodic reduction of the PdO intermediates. The obtained Pd‐NCs are soluble in either polar or non‐polar solvents, depending on the selected capping ligands. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>